RELIGIOUS PRACTICES IN THE SATAVAHANA EMPIRE - Suresha, T M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Satavahana Empire, which flourished between the 2nd century BCE and the 2nd century CE in the Deccan region of India, was characterized by a diverse and syncretic religious landscape. The empire, with its strategic location as a cultural crossroads, saw the integration of various religious practices, including Brahmanism, Buddhism, Jainism, and regional folk traditions. The Satavahana rulers, particularly kings like Gautamiputra Satakarni, were known for their religious tolerance and active patronage of multiple faiths, which played a crucial role in solidifying their political power and maintaining social cohesion. Brahmanism, the precursor to Hinduism, was strongly supported by the Satavahana kings, who performed Vedic rituals and sacrifices to legitimize their rule. Royal patronage extended to the construction of temples, and the worship of deities like Surya (the Sun God) and Siva became prominent. Simultaneously, the Satavahanas were notable patrons of Buddhism, commissioning the construction of stupas, viharas, and chaityas, particularly in centers like Amaravati and Nagarjunakonda. These monuments, with their rich carvings and sculptures, not only served religious purposes but also represented the empire's artistic achievements. The Satavahanas also supported Jainism, reflecting the pluralistic nature of their reign. Jain monks and nuns were provided with the freedom to practice and spread their teachings, contributing to the religious diversity of the empire. Additionally, the royal patronage of religious institutions served to enhance the empire's prestige, with religious rituals and donations often being recorded in inscriptions. The Satavahana Empire's religious practices, blending indigenous traditions with influences from trade and foreign interactions, laid the foundation for the cultural and religious developments of South India, making the empire a significant chapter in the history of Indian religion.